Production of killer toxin from DSMZ70238 Debaryomyces hansenii and test the effectiveness against cancer cell line L20B. - Wijdan H. Abdul-Razzak; Jamal A. Ibraheem; Safa-Ulddin A. Shanter (مجلة جامعة الانبار للعلوم الصرفة, 2018)
This study was conducted to detect the ability of yeast Debryomyces hansenii DSMZ70238 to produce the killer toxin and testing the optimal conditions for production rather than studying the cytotoxicity toward the cancer cell line L20B. The optimal conditions studied for their effect on yeast growth rates and their ability to increased production of killer toxin included different concentrations of NaCl salt, glucose, different concentrations of pH as well as different temperatures. The results showed that the killer yeast had the ability to produce the killer toxin in the molecular weight of 22 KDa were detected by the using of 12% SDS Polyacryelamide Gel, The optimal conditions of the production was studied and the killing activity of this toxin was determined towards microbes used in the present study, The results showed 8% of salts, pH 4.5, Temperature 25 ͦ C and 10 % from carbon source (glucose) are the best conditions for production and the killing activity. To detect the killing activity of killer toxin toward the cancer cells, The cytotoxicity test of the killer toxin was investigated against the cell line (L20B), by using the partially purified concentrated killer toxin produced under optimal conditions, The results of this experiment showed the killer toxin has a lethal effect of cancer cells, which reached the highest percentage at 8% salts concentration and it was 47.61% and at pH 4.5 reached 23.07%, while the percentage of killing was 21.53% at 25 ͦ C and 47.30% at 10% of glucose concentration.